Analisis Air Leakage Terhadap Unjuk Kerja Air Preheater A Sebelum Dan Sesudah Overhaul Di Pltu Adipala 1 X 660 Mw PT. PLN (Persero) - ERI - PRABOWO (Sekolah Tinggi Teknik - PLN, 2020)
The efficiency of boilers in steam power plants dependents on the utilization of heat from the exhaust gas by the air heater or the air preheater. To improve the air preheater efficiency can be achieved by increasing performance which is by minimizing leakage on the air preheater so that it will increase the heat transfer rate because the heating element receives heat from the flue gas without reducing the gas flue flow resulting from the leakage increased, so that it will have an impact on increasing the efficiency of the air preheater. The effect of air leakage is not only on the efficiency of the air heater but also on the efficiency of the generator. This is due to the addition of flow from ID fans, FD fans and PA fans which results in wasteful power consumption which reduces plant efficiency. In Central Java PLTU 2 Adipala there is an increase in air leakage because the seals on the air preheater are not properly installed, therefore when overhauled, seal repairs are carried out to reduce water leakage on the air preheater. On the air preheater there are axial seals and radial seals which have the same role of reducing leakage on the air preheater by doing repairs to the seal, it will reduce air leakage which has an impact on increasing the air preheater efficiency and efficiency of the plant. In a steam power plant (PLTU) system, the air preheater has an important role, that is, if there is a decrease in performance it will affect the efficiency of the boiler which will have an impact on the power produced by the power plant, it is necessary to overhaul the air preheater to maintain the reliability of the equipment.